Australia’s Pacific Step-Up Foreign Policy as a Response to the Increase of China’s Influence in the Pacific - Wulandari, Meinita Hasya Eka; Saragih, Hendra Maujana (Insignia: Journal of International Relations, 2023)
The Pacific region has become highly geopolitical due to its economic, strategic, and military significance. Pacific Island countries face several challenges that they are striving to address because many Pacific Island nations have limited resources in terms of finances and skilled human resources, lack of access to technology, capacity building, and economic development, on the other side is prone to natural disasters such as cyclones, tsunamis, and earthquakes, also face challenges in providing adequate healthcare and education services, and are especially vulnerable to climate change whose impact may vary. The issue then becomes the reason for regional and global powers like Australia and China to exercise their capability and aim to fulfill their respective national interests to extent their influence in the region through their foreign policy. Influence pertains to a country’s ability to affect other nations' or international entities' decisions, actions, and behaviors. This research uses qualitative methods and foreign policy theory to address the issue further. In this research, Australia emphasizes its foreign policy to the Pacific using The Pacific Step-Up programme to pursue their interest as a long-standing partner and its neighborhood’s guardians and counter China’s growing presence and influence in the region. Keywords: Australia, China, foreign policy, Pacific